OPTIMIZING DUTY RATIOS IN A GRID-INTERACTIVE INVERTER: A FIVE-LEVEL, THREE-LEG, THREE-PHASE CASCADED H-BRIDGE APPROACH EMPLOYING MPCC WITH AN EXPLICIT INTEGRATION ALGORITHM - Edmund Kwafo ADJEI-SAFORO; Francis Boafo EFFAH; Misbawu ADAM; Ebrahimpanah SHAHROUZ; Emmanuel Asuming FRIMPONG (Carpathian Journal of Electrical Engineering, 2023)
The model predictive current control stands out as a robust control strategy extensively applied in the enhancement of various industrial applications. Renowned for its capacity to handle multiple inputs and generate multiple outputs (MIMO), it is recognized for its consistently excellent performance and unique stable control techniques. However, the computational intensity required to remedy an optimization task at each time step poses a potential drawback, impacting its suitability for real-time control applications and potentially affecting system performance. This study introduces the concept of duty cycle optimization, leveraging the explicit integration approximation. This involves the application of rectangular voltage for both non-zero as well as zero within one control period to minimize current ripples in the grid-interactive system. Additionally, error minimization is achieved through the selection of the duration for the two-rectangular voltage. Experimental and simulation results validate the substantial reductions in ripple current as well as total harmonic distortion achieved through this approach.